Production of ochratoxin A in dry-cured ham based-media by Aspergillus westerdijkiae - Vipotnik, Ziva (2018)
﻿﻿Ochratoxin A (OTA) is a secondary metabolite produced by Penicillium and Aspergillus genera and is considered one of the most important mycotoxins occurring in animal and human food chains. Oxidative stress, inhibition of protein synthesis, disruption of calcium homeostasis, inhibition of mitochondrial respiration and DNA damage are some of OTA´s mechanisms of action causing teratogenicity, immunotoxicity, neurotoxicity and mostly nephrotoxicity. In dry-cured and fermented meat products, OTA is strongly associated with Penicillium nordicum (PN), but Aspergillus westerdijkiae (AW), a strong OTA producer usually associated with contamination of coffee beans, has also been found to be responsible for high OTA levels in cured meat products. Fungal growth and OTA production in meat products can be influenced by environmental conditions, physico-chemical characteristics of the matrix, and its endogenous flora. OTA is highly stable, so its destruction during normal food processing is very difficult to achieve.